2018
DOI: 10.30519/ahtr.440123
|View full text |Cite
|
Sign up to set email alerts
|

Use of Menu Design Techniques: Evidences from Menu Cards of Restaurants in Alanya

Abstract: This study aims at identifying the existence of menu design techniques in actual menu cards, and to question whether use of those techniques is intentional. In total, 86 menu cards were collected from restaurants located in Alanya which is a tourist resort in Antalya, Turkey. Both qualitative and quantitative analyses were performed. First, content analysis was utilized to categorize the qualitative data, and second logistic regression was conducted to test the prescribed relations between menu variety and exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
1
5
0
2
Order By: Relevance
“…However, the café's operators paid little attention to this in positioning items on the menu card. Instead, the participants explained that they placed the products they wanted to sell most at the top, which is similar to the findings of Özdemir and Nebioğlu (2018), who examined 86 restaurant menus, and concluded that the strategic locations of the items were not consciously selected. They suggested that this was because the graphic layout of the menu was more prominent than strategic positioning.…”
Section: Theoretical Implicationssupporting
confidence: 62%
See 3 more Smart Citations
“…However, the café's operators paid little attention to this in positioning items on the menu card. Instead, the participants explained that they placed the products they wanted to sell most at the top, which is similar to the findings of Özdemir and Nebioğlu (2018), who examined 86 restaurant menus, and concluded that the strategic locations of the items were not consciously selected. They suggested that this was because the graphic layout of the menu was more prominent than strategic positioning.…”
Section: Theoretical Implicationssupporting
confidence: 62%
“…To the best of the author's knowledge, this is the first empirical test of the Menu Management Process Model. In addition, most empirical studies of menus are made from the consumer's perspective rather than the business perspective (Özdemir & Nebioğlu, 2018). Therefore, the present study can contribute to the literature by examining the model from the perspective of operators.…”
Section: Menu Management Process Modelmentioning
confidence: 98%
See 2 more Smart Citations
“…These service dimensions determine the dining behavior and revisit intention of the clientele. Moreover, the studies on restaurants (Namin, 2017) have reached to the conclusion that menu (ÖZDEMİR & NEBİOĞLU, 2018) and atmosphere (Dutta et al, 2014) affect customers' satisfaction. Based on the conclusion of aforementioned studies, there is a need to comprehend the potential impact of quality of food, quality of service, atmosphere, price, as well as variety of food on customers' satisfaction regarding fast-food restaurants.…”
Section: Introductionmentioning
confidence: 99%